A Chaperone Complex Formed by HSP47, FKBP65, and BiP Modulates Telopeptide Lysyl Hydroxylation of Type I Procollagen. (6th April 2017) - Duran, Ivan; Martin, Jorge H; Weis, Mary Ann; Krejci, Pavel; Konik, Peter; Li, Bing; Alanay, Yasemin; Lietman, Caressa; Lee, Brendan; Eyre, David; Cohn, Daniel H; Krakow, Deborah
ABSTRACT: Lysine hydroxylation of type I collagen telopeptides varies from tissue to tissue, and these distinct hydroxylation patterns modulate collagen cross‐linking to generate a unique extracellular matrix. Abnormalities in these patterns contribute to pathologies that include osteogenesis imperfecta (OI), fibrosis, and cancer. Telopeptide procollagen modifications are carried out by lysyl hydroxylase 2 (LH2); however, little is known regarding how this enzyme regulates hydroxylation patterns. We identified an ER complex of resident chaperones that includes HSP47, FKBP65, and BiP regulating the activity of LH2. Our findings show that FKBP65 and HSP47 modulate the activity of LH2 to either favor or repress its activity. BiP was also identified as a member of the complex, playing a role in enhancing the formation of the complex. This newly identified ER chaperone complex contributes to our understanding of how LH2 regulates lysyl hydroxylation of type I collagen C‐telopeptides to affect the quality of connective tissues. © 2017 American Society for Bone and Mineral Research.